Constitution of Long COVID illness, patienthood and recovery: a critical synthesis of qualitative studies - Harrison, Mia; Rhodes, Tim; Lancaster, Kari (BMJ open, 2024)
ObjectivesTo investigate the lived experiences of Long COVID.DesignCritical interpretive synthesis of qualitative research.Data sourcesPubMed and Web of Science databases were searched on 14 September 2023.Eligibility criteriaOriginal peer-reviewed qualitative studies describing the experiences of Long COVID were eligible for inclusion.Data extraction and synthesisWe used established qualitative synthesis methods to search, screen and manually code the included studies. Critical interpretation methods were used to analyse the data and develop synthetic constructs.Results68 articles were identified in the first phase of sampling, with 16 studies and 879 participants included in the final synthesis. The analysis of these studies was organised into three thematic constructions of Long COVID: (1) the illness, (2) the patient and (3) recovery. Long COVID was diversely characterised across study approaches, designs and findings but was underpinned by shared diagnostic logics, which shaped the identification and measurement of symptoms. The boundaries between different constitutions of Long COVID in qualitative accounts of illness experience were often imprecise. Slippages between different definitions of Long COVID had implications for patient experiences in relation to diagnosis, help-seeking and care, and expectations of recovery.ConclusionsLong COVID is a site of multiple and diverse qualitative interpretation. Accounts of lived experience emphasise the constitutions of illness, patienthood and recovery as situated and emergent. The ongoing context-based negotiation of Long COVID is a defining qualitative feature of the condition. Approaches to researching, diagnosing and developing health interventions must be as adaptive as the varieties of Long COVID lived experience.